Efektivitas Pembelajaran Musik Terhadap Pengembangan Kreativitas Siswa MTS di Kabupaten Lombok Utara - Fikhan Ghazali; Gading Suryadmaja; Muhammad Fajar Putranto (MANDALA WIDYA: Jurnal Ilmu Pendidikan, 2026)
This study aims to analyse the effectiveness of music learning in fostering the creativity of Madrasah Tsanawiyah (MTs) students in North Lombok Regency, with a case study conducted at MTs Al Baqiatusshalihat NW Santong. Creativity is conceptualised as a key competency in 21st-century education, encompassing divergent, original, and flexible thinking, and is closely related to the cognitive and affective development of madrasah students. The study employs a quantitative approach using a quasi-experimental design. The research participants were MTs students who engaged in music learning activities grounded in creative practices, including rhythm exploration, musical improvisation, and simple composition. Students’ creativity data were collected through a creativity test instrument measuring fluency, flexibility, and originality, and were analysed using statistical tests to examine differences before and after the intervention. The findings indicate that music learning has a positive and statistically significant effect on enhancing students’ creativity. These results confirm that music learning functions not only as a means of developing aesthetic skills but also as an effective pedagogical strategy for supporting creativity development among MTs students. Accordingly, this study recommends strengthening music education within the madrasah curriculum as an integral component of holistic and multidisciplinary education